TECHNOLOGY FOR WORKING WITH PEOPLE WITH DISABILITIES - Khakimov , Orziqul; Gurgiboyev, Otabek (Science technology&Digital finance, 2023)
This article describes the restoration and adaptation of the social rights of children and young people with disabilities to the social environment as one of the most pressing issues of the present day. According to statistics, the number of children with disabilities is observed to increase every year. According to the researchers, the main reasons for the occurrence of disability in children are the deterioration of the environmental situation, the increase in child injury and the inadequacy of women's working conditions.